VERIFICATION OF POLITICAL PARTIES PARTICIPATING IN GENERAL ELECTIONS BEFORE AND AFTER THE DECISIONS OF THE CONSTITUTIONAL COURT: VERIFIKASI PARTAI POLITIK PESERTA PEMILIHAN UMUM SEBELUM DAN SESUDAH PUTUSAN MAHKAMAH KONSTITUSI - Yusuf Mulya Kharismawan (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2023)
Political parties are the political superstructure of a democratic country, namely as a means for citizens to occupy political positions through general elections. The requirements for passing verification as election participants by the General Elections Commission must be met by political parties contained in the election law, by making it harder for political parties to pass verification as well as exceptions for several political parties that have met certain verification requirements so that they are immediately designated as participants to next elections. The exception is not in accordance with Article 27 paragraph (1), Article 28D paragraph (1) and Article 28D paragraph (3) of the 1945 Constitution as unconstitutional through several decisions of the Constitutional Court. The purpose of this study is to determine the conditions for passing the verification of political parties participating in the General Election before and after the Constitutional Court Decision, and analyze the considerations of the Constitutional Court judges regarding the requirements to pass the verification of political parties participating in the General Election based on the principle of equal treatment before the law, using a normative approach. It can be concluded that the considerations of the Constitutional Court regarding the verification requirements of political parties participating in the general election are inconsistent because the material test of the 1945 Constitution used are different and there is not required for the Constitutional Court to use jurisprudence as a basis for consideration even though there are similarities in substance.